Diagnostics of group A beta-hemolytic streptococci and their resistence pattern in Yogyakafta - Suparwoto Saleh, Suparwoto Saleh (Universitas Gadjah Mada, 1987)
Pharyngitis or impetigo caused by group A beta-hemolytic streptococci can incite acute rheumatic fever or acute glomerulonephritis. The Microbiology Department, Gadjah Mada University Faculty of Medicine, has identified and tested the sensitivity of group A beta-hemolytic streptococci to various antibiotics. Forty-one strains of group A beta-hemolytic streptococci (12.6%) resulted from 326 throat swabs could be isolated; and 4 strains of the streptococci (40%) resulted from 10 skin swabs could be found. The other 19 strains were Rested by various antibiotics. It was found that there was not any strain which could resist penicillin G. One strain having been tested could resist erythromycin (5.3%). All strains were also sensitive to arnpicillin, cephalexin, cefotaxime, gentamicin and vancornycin. The resistence to amikacin and chloramphenicol was quite high: 5B% and 26.3%. while the resistence to tetracyclin seemed to be the highest, which was 89.5%. Key Words: group A beta-hemolytic streptococci - acute rheumatic fever - bacute glomerulonephritis - penicillin G - erythromycin